Molecular Comparison among Three Antarctic Endemic Springtail Species and Description of the Mitochondrial Genome of Friesea gretae (Hexapoda, Collembola) - Antonio Carapelli; Claudio Cucini; Pietro Paolo Fanciulli; Francesco Frati; Peter Convey; Francesco Nardi (Diversity, 2020)
Springtails and mites are the dominant groups of terrestrial arthropods in Antarctic terrestrial ecosystems. Their Antarctic diversity includes a limited number of species, which are frequently endemic to specific regions within the continent. Advances in molecular techniques, combined with the re-evaluation of morphological characters and the availability of new samples, have recently led to the identification of a number of new springtail species within previously named, but ill-defined, species entities described in the last century. One such species, the neanurid Friesea grisea, originally described from sub-Antarctic South Georgia, was for many years considered to be the only known springtail with a pan-Antarctic distribution. With the recent availability of new morphological and molecular data, it has now been firmly established that the different representatives previously referred to this taxon from the Antarctic Peninsula and Victoria Land (continental Antarctica) should no longer be considered as representing one and the same species, and three clearly distinct taxa have been recognized: F. antarctica, F. gretae and F. propria. In this study, the relationships among these three species are further explored through the sequencing of the complete mtDNA for F. gretae and the use of complete mitogenomic as well as cytochrome c oxidase I data. The data obtained provide further support that distinct species were originally hidden within the same taxon and that, despite the difficulties in obtaining reliable diagnostic morphological characters, F. gretae is genetically differentiated from F. propria (known to be present in different locations in Northern Victoria Land), as well as from F. antarctica (distributed in the Antarctic Peninsula).